ENHANCING ACTIVITIES TYPES OF TEACHERS USING COOPERATIVE JIGSAW IN CLASS VIA - Nayuk Sestuningsih; Dwi Kameluh Agustina; Minto Santoso (Universitas Islam Balitar, 2019)
Application of jigsaw cooperative learning is done to increase the activity of teachers. The method used is qualitative descriptive method to describe the condition of the activity of teachers in the learning theme 8 sub themes 1. This type of research is